2007
DOI: 10.1088/0953-8984/19/15/156222
|View full text |Cite
|
Sign up to set email alerts
|

Optical effects of annealing on Yb-doped Y2SiO5thin films

Abstract: In this paper we investigate the optical effects of annealing under an oxygen atmosphere of Yb-doped Y2SiO5 thin films grown by liquid phase epitaxy. Infrared transmission, particularly adapted to thin film characterizations by means of Yb3+ crystal field excitations, is used to single out the effects of annealing. For instance, absorption intensities increase by ∼10% and disorder in Yb3+ substitution is reduced. Micro-Raman backscattering measurements detect no particular defects in as-grown and annealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Incorporation of Yb into ceramic-based (YAG [11,12,13], Y 2 SiO 5 (YSO) [14,15,16], KY(WO 4 ) 2 [17], NaLu(WO 4 ) 2 [18], and Al 2 O 3 [19,20]) wide bandgap semiconductors, oxide-based semiconductors (ZnO [21,22,23], TiO 2 [24,25], In 2 O 3 [26]), III–V group based materials (AlN [27]), and Si-based [28] thin film hosts using various deposition techniques, have been shown to produce luminescence at a wavelength of around 1 μm. For Yb doped YAG [11], YSO [14,15], and KY(WO 4 ) 2 [17] thin films, the liquid phase epitaxial (LPE) method has been employed to fabricate homogeneous crystalline films from a molten solute diluted in a solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of Yb into ceramic-based (YAG [11,12,13], Y 2 SiO 5 (YSO) [14,15,16], KY(WO 4 ) 2 [17], NaLu(WO 4 ) 2 [18], and Al 2 O 3 [19,20]) wide bandgap semiconductors, oxide-based semiconductors (ZnO [21,22,23], TiO 2 [24,25], In 2 O 3 [26]), III–V group based materials (AlN [27]), and Si-based [28] thin film hosts using various deposition techniques, have been shown to produce luminescence at a wavelength of around 1 μm. For Yb doped YAG [11], YSO [14,15], and KY(WO 4 ) 2 [17] thin films, the liquid phase epitaxial (LPE) method has been employed to fabricate homogeneous crystalline films from a molten solute diluted in a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…For Yb doped YAG [11], YSO [14,15], and KY(WO 4 ) 2 [17] thin films, the liquid phase epitaxial (LPE) method has been employed to fabricate homogeneous crystalline films from a molten solute diluted in a solvent. Their growth and post-deposition annealing temperatures are as high as 900–1300 °C so as to avoid growth defects and to further improve the film quality [11,14,15]. In addition, a flat oriented YAG and/or YSO single crystalline substrate is needed as a seed in the LPE method, since growth of the single crystal film is performed by dipping the substrate in a supersaturated melt solution [29].…”
Section: Introductionmentioning
confidence: 99%
“…Yb-doped Y 2 SiO 5 (YSO:Yb) thin films and single crystals have been recently studied by Raman spectroscopy and infrared transmission [2][3][4]. In particular, the crystal-field (CF) levels of the two Yb 3+ ions occupied sites in Y 2 SiO 5 (YSO) have been detected with their vibronic side bands, and Yb 3+ -Yb 3+ magnetically coupled pairs have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Yb 3+ ions enter the two non-equivalent and equally populated Y I and Y II sites of C 1 symmetry in Y 2 SiO 5 [14]. According to preliminary infrared absorption studies of YSO:Yb [3,4], in addition to Yb I and Yb II isolated ions absorption bands around 10,189 and 10,215 cm À1 , respectively, the presence of interacting Yb 3+ -Yb 3+ pairs is manifest in satellite absorption bands (e.g. 10,206 and 10,220 cm À1 ) located at D+J/2 and DÀ3J/2, where D corresponds to the Yb 3+ isolated ion CF transition and J to the pair-exchange coupling constant [15].…”
Section: Introductionmentioning
confidence: 99%
“…23 Some studies have reported the preparation and luminescence properties of the rare-earth doped Y 2 SiO 5 films. [24][25][26][27][28][29][30] These previous efforts had mainly been focused on the one-photon excited down-conversion spontaneous emission. However, the up-conversion spontaneous emission in Y 2 SiO 5 :Yb, Er inverse opal photonic crystals has not yet been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%